2014
DOI: 10.1037/a0037113
|View full text |Cite
|
Sign up to set email alerts
|

Differential time scales of change to learning frequency structures of isometric force tracking.

Abstract: Multiple processes support the persistent (learning) and transient (adaptive) change in behavior over time. We investigated whether practice and rest influence similarly the learning and adaptation of slow and fast frequency structures in isometric force tracking of pathways that varied in their regularity. Participants practiced 25 trials on each of 5 days in either a constant force target or 1 with the 1/f distributional properties of brown or pink noise. There was a reduction in root mean squared error (RMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…A key question that requires further exploration is how these oscillatory time scales of force control interact with the growth/decay time scales of learning and development . The current findings provide further evidence that the oscillatory time scales of motor output show different characteristics of growth/decay time scales of learning (Studenka et al, 2014).…”
Section: Informational Constraints and Transfermentioning
confidence: 53%
See 4 more Smart Citations
“…A key question that requires further exploration is how these oscillatory time scales of force control interact with the growth/decay time scales of learning and development . The current findings provide further evidence that the oscillatory time scales of motor output show different characteristics of growth/decay time scales of learning (Studenka et al, 2014).…”
Section: Informational Constraints and Transfermentioning
confidence: 53%
“…The principal questions were whether (a) practice would differentially alter the multiple time scales of force output as well as interact with the visual scaling manipulation (Hu & Newell, 2010); (b) the selective visual scaling manipulation would generalize across the multiples time scale of force output in a manner consistent with fractal models of physiology and behavior (Bassingthwaighte et al, 1994;Ward, 2002); and (c) the selective visual scaling manipulation of the practice environment would induce enhanced transfer to novel task conditions compared to the fixed gain group. Practice and force output structure Previous studies have shown bidirectional changes (Newell & Vaillancourt, 2001) and differential time scales of learning (Studenka et al, 2014) of isometric force dynamics as a function of practice. Here, task outcome (RMSE) showed reductions of error over practice (block and day) as well as an interaction between practice and visual scaling conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations